Pengaruh Penambahan Tepung Tulang Ikan Gabus (Channa striata) terhadap Karakteristik Mie Basah Labu Kuning - Kholifah, Chintya Ayu; Rosidah, Umi (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2022)
Kholifah AC, Rosidah U. 2022. The effect of snakehead fish bones flour (Channa striata) on characteristics of pumpkin wet noodles. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 346-.357. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).This study aimed to find out the effect of the addition of snakehead fish bone meal on the characteristics of pumpkin wet noodles. This study used a Complete Non-Factorial Randomized Design (RALNF) with one treatment factor, namely the addition of snakehead fish bone meal with repeats as much as 3 times. The concentration of addition of snakehead fish bone meal is 0%, 5%, 10%, 15%, 20%.25%. The parameters observed in the study were physical parameters and chemical parameters. The results showed that the addition of snakehead fish bone meal had a real effect on the physical characteristics of color, hardness, tensile strength and chemical characteristics, namely water content, ash content, calcium content and protein content of pumpkin wet noodle. The results showed that the higher the addition of snakehead fish bone meal, the increase in hardness value, water content, ash content, protein content in pumpkin wet noodles consecutively 26.47 gf to 34.93 gf, 58.57% to 70.49%, 0.91% to 5.63%, 8.95% to 10.74%. The average of calcium content in wet noodles of pumpkin increased by 2.46% to 5.91 along with the higher addition of snakehead fish bone meal. The strong average value of wet noodle pull decreased along with the addition of snakehead fish bone meal by 0.057 MPa to 0.027 MPa.